Integration of singular enrichment functions in the generalized/extended finite element method for three-dimensional problems - Park, Kyoungsoo; Pereira, Jeronymo P.; Duarte, C. Armando; Paulino, Glaucio H. (International journal for numerical methods in engineering, 2009)
A mapping method is developed to integrate weak singularities, which result from enrichment functions in the generalized/extended finite element method. The integration scheme is applicable to 2D and 3D problems including arbitrarily shaped triangles and tetrahedra. Implementation of the proposed scheme in existing codes is straightforward. Numerical examples for 2D and 3D problems demonstrate the accuracy and convergence properties of the technique. Copyright © 2008 John Wiley & Sons, Ltd.